TEMA CERPEN DALAM ANTOLOGI DODOLITDODOLITDODOLIBRET DAN KELAYAKANNYA SEBAGAI BAHAN AJAR SASTRA - Dwi Prihatini; Kahfie Nazaruddin; Edi Suyanto (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
Problem in this research is how each of a short story’s theme depicted in the short story collection in Dodolitdodolitdodolibret and its feasibility as teaching material of Bahasa dan Sastra Indonesia in senior high school. This research aims to describe the themes that exist in the short story collection in Dodolitdodolitdodolibret and to determine its feasibility as teaching material in senior high school. The research method being used is descriptive method. Source of data used is the short story collection in Dodolitdodolitdodolibret, totaling 18 titles of short stories, published in 2011, 210 pages thick, and published by Penerbit Buku Kompas. The result of the research showed that deductively themes in the short story collection in Dodolitdodolitdodolibret can be categorized into 4 types consisting of (a) theme of divine, (b) social theme, (c) physical themes, (d) organic theme. The short story collection in Dodolitdodolitdodolibret deserve to be used as the alternative teaching material of Bahasa dan Sastra Indonesia in senior high school because it fulfill the criteria of character education, Kurikulum Tingkat Satuan  Pendidikan (KTSP), language aspect, psychological aspect, and aspect of cultural background.Key word : theme, feasibility, short story